2015
DOI: 10.1002/2015ja021533
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of ring current ion energy density and energy content during geomagnetic storms based on Van Allen Probes measurements

Abstract: Enabled by the comprehensive measurements from the Magnetic Electron Ion Spectrometer (MagEIS), Helium Oxygen Proton Electron mass spectrometer (HOPE), and Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) instruments onboard Van Allen Probes in the heart of the radiation belt, the relative contributions of ions with different energies and species to the ring current energy density and their dependence on the phases of geomagnetic storms are quantified. The results show that lower energy (<50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(142 citation statements)
references
References 65 publications
(88 reference statements)
12
129
0
1
Order By: Relevance
“…The horizontal axis represents the scale in minutes and the vertical axis represents the crosscorrelation coefficient. So, even when there is no magnetic reconnection happening, the protons which are more active during the quietest period, present in the inner ionosphere, trigger the ring current that assists in depression of SYM-H value and positive correlation with magnetospheric energy deposition Ur, Uj, and Ua (Zhao et al, 2015). The plot is not symmetric with more inclination in the negative side of time scale.…”
Section: Correlationmentioning
confidence: 94%
See 1 more Smart Citation
“…The horizontal axis represents the scale in minutes and the vertical axis represents the crosscorrelation coefficient. So, even when there is no magnetic reconnection happening, the protons which are more active during the quietest period, present in the inner ionosphere, trigger the ring current that assists in depression of SYM-H value and positive correlation with magnetospheric energy deposition Ur, Uj, and Ua (Zhao et al, 2015). The plot is not symmetric with more inclination in the negative side of time scale.…”
Section: Correlationmentioning
confidence: 94%
“…Other than geomagnetic depression, such activity cause life-threatening power outages and satellite damage, communication failures and navigational problems (Lakhina & Tsurutani, 2016). The ring current is a near equatorial electric current flowing toroidally around the Earth, formed by charge particle pressure gradients and drift motion (Zhao et al, 2015). These currents lead to deposition of energy in different forms such as ring current energy, joule heating, and auroral precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2015) showed that energy ranges that make the dominant contribution from H+ to the total energy density are higher at L = 3 and L = 4 than at L = 5 and 5.8 during a moderate storm on 29 March 2017. The spatial characteristics of contributing energies can be explained by adiabatic transport of plasma sheet ions during which lower-energy ions can penetrate more deeply into the inner magnetosphere than higher-energy ones due to relatively lower magnetic field drifts (i.e., curvature and gradient-B drifts).…”
Section: 1029/2018gl080047mentioning
confidence: 98%
“…This perturbation can be considered as a rough equivalent to the Dst-index if it is assumed (Carovillano and Siscoe 1973) that it is close to the perturbation averaged around the equator of the Earth. The DPS relation was used in numerous studies for Dst-index estimates from modeling and observations and related ring current dynamics (e.g., Greenspan and Hamilton 2000;Ebihara and Ejiri 2000;Fok et al 2001b;Jordanova et al 2012;Ganushkina et al 2012;Katus et al 2015;Zhao et al 2015). However, the Dst-index contains contributions from many other sources than the azimuthally symmetric ring current and their contributions can be significant or even largest during disturbed conditions.…”
Section: Dst-index As a Storm Indicator Measure And Predictormentioning
confidence: 99%
“…Although, the early measurements of the ring current particles were made onboard OGO 3 (e.g., Frank 1967), Explorer 45 (e.g., Smith and Hoffman 1974) and CRRES missions (e.g., Grande et al 1997;Friedel and Korth 1997), the first mission, which clarified the detailed picture of the ring current energy and composition was the AMPTE mission of the late 1980s (e.g., Lui et al 1987;Lui and Hamilton 1992;De Michelis et al 1997). Extensive observations of the ring current were done by the most recent Van Allen Probes mission (e.g., Zhao et al 2015;Gkioulidou et al 2016;Kistler et al 2016;Shi et al 2016;Menz et al 2017). …”
Section: Ring Current In the Earth's Magnetosphere: Brief Reviewmentioning
confidence: 99%